2011
DOI: 10.1080/00207233.2011.591898
|View full text |Cite
|
Sign up to set email alerts
|

Rainwater and the resulting runoff chemistry in Shiraz city, southwest Iran

Abstract: Samples were collected from rainwater, the resulting runoff in urban drainage channels and the Khoshk River (a seasonal river which passes through the city and receives urban drainage channels runoff). Major elements and selected heavy metals (Cu, Pb and Zn) concentrations were investigated for rainwater samples. Marine and non-marine sources of the elements in rainwater were investigated by calculation of Sea salt fraction, Non sea salt fraction and application of factor analysis. pH and mean concentrations o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
3
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 38 publications
2
3
1
Order By: Relevance
“…Based on the results of a similar study conducted in 2011 in Shiraz by Moore et al, it can be concluded that the concentrations of Zn and Cu have increased by 3.5 and 2.3 times (respectively) from 2011 until today. This increase can be attributed to an increase in motor vehicle use and industrial activities during these years [37, 38]. In contrast, the concentration of Pb in this study is slightly lower than those reported by Moore et al This can be attributed to the improvement in the quality of gasoline and a ban the use of leaded gasoline in vehicles.…”
Section: Resultscontrasting
confidence: 71%
“…Based on the results of a similar study conducted in 2011 in Shiraz by Moore et al, it can be concluded that the concentrations of Zn and Cu have increased by 3.5 and 2.3 times (respectively) from 2011 until today. This increase can be attributed to an increase in motor vehicle use and industrial activities during these years [37, 38]. In contrast, the concentration of Pb in this study is slightly lower than those reported by Moore et al This can be attributed to the improvement in the quality of gasoline and a ban the use of leaded gasoline in vehicles.…”
Section: Resultscontrasting
confidence: 71%
“…This is due to the road surface, dust, and soil that exist in the surface. Similar phenomenon was observed in Iraq [31] as the alkalinity that exists in the dust may transfer through the runoff of the rainwater and from there to the other water bodies. FOGs concentration is more than 5 ppm which in the maximum concentration for agricultural proposed.…”
Section: Resultssupporting
confidence: 71%
“…While δ 15 N in rainwater samples, ranging between + 9.6 and + 10.8 ‰ (Table 4), is compatible with results from previous studies (e.g. [24]), the corresponding δ 18 O, ranging from + 4.5 to + 7.9 ‰ (Table 4), is significantly depleted in 18 O which may indicate a non-negligible amount of NH 4 + in rainwater [36], consistent with air pollution observed over industrial cities in Iran such as Shiraz impacting its chemical composition [51,52]. Their δ 15 N and δ 18 O are similar to those measured in the spring water sample (δ 15 N = + 7.7 ‰ and δ 18 O = + 3.5 ‰).…”
supporting
confidence: 92%